Class - Joyce Patrick (Oxford University Press, 1995)
Introduction, The Classical Inheritance and Its Development, An Inheritance In Question, Class and the Historians, The History of the Socials, The Hermeneutics of the Social: Codes and Categories, The Language of Class, Selected Reading List, Biographical Notes, Acknowledgements, Index.